PENGARUH UKURAN POLYBAG TERHADAP PERTUMBUHAN VEGETATIF SAWI PAKCOY (BRASSICA RAPA L.) - THERESIA SUZANNA CATHARINA; NARITA AMNI ROSADI; IDA AYU NOPIARI (Universitas Mahasaraswati K. Mataram, 2023)
Horticultural crops are very popular plants. One of the leading horticultural products in the agricultural sector in Indonesia is vegetable crops. Green mustard pakcoy (Brassica rapa L.) is a vegetable plant that is very easy to breed in cold and hot areas, at an altitude of 500 m to 1200 m above sea level. Limited land for planting mustard pakcoy (Brassica rapa L.), for daily needs can be planted in polybags. The size of the polybag used needs to be considered. The experiment was carried out in a green house at KWT Jeruk Manis on Jl Dukuh Saleh Pejeruk Ampenan. The variables observed included: average plant height, average number of leaves, average leaf width and fresh plant weight. The measurement data were analyzed using analysis of variance (CRD) and DMRT further test. From the results of the analysis, the experimental results showed that the size of a small polybag 15 x 20 cm had a significant effect on the observed variables, namely plant height (cm), number of leaves (strands), leaf width, and mustard greens